Peran Peraturan Daerah dalam Perlindungan Hak Asasi Manusia di Era Otonomi Daerah - Najiib, Alfian Naufal; Pradana, Ardiva Galih; Ramdhani, Helmy Rizal; Ramdhani, Fahmi Ali (Innovative: Journal Of Social Science Research, 2025)
The era of regional autonomy has given broader authority to regional governments to regulate and manage government affairs in accordance with the principle of decentralization. In the context of protecting human rights, regional regulations (Perda) have a strategic role as a legal instrument that can guarantee the protection, fulfillment, and enforcement of human rights at the local level. This study uses a normative juridical method with a statutory and conceptual approach to analyze the position of Perda in the national legal system and its correlation with the principles of regional government law. The analysis was carried out on various related regulations, starting from the 1945 Constitution, Law No. 23 of 2014 concerning Regional Government, Law No. 39 of 1999 concerning Human Rights, to various Perda that have been issued by regional governments in Indonesia. The results of the study indicate that Perda has a dual function in protecting human rights, namely as an operationalization of the authority of regional governments in carrying out mandatory human rights protection affairs as well as a bridge for the implementation of universal human rights norms into the local context. However, there are significant challenges in harmonizing Regional Regulations with the hierarchy of national laws and regulations, especially in ensuring that Regional Regulations do not conflict with higher regulations and remain in line with the principles of the rule of law. The effectiveness of human rights protection through Regional Regulations also depends heavily on the institutional capacity of regional governments, community participation in the process of forming Regional Regulations, and comprehensive monitoring and evaluation mechanisms. This finding implies the need to strengthen synergy between the central and regional governments in creating a legal ecosystem that is conducive to sustainable human rights protection in the era of regional autonomy.